Implementasi Gentle Parenting dalam mengoptimalkan perkembangan emosional anak usia dini: Pendekatan berbasis kasih sayang dan komunikasi efektif - Fitria, Laila Nur (Maliki Interdisciplinary Journal, 2025)
Gentle parenting is a parenting style with an approach that emphasizes affection, open communication, and the formation of a strong emotional connection between parents and children. This article aims to analyze the impact of gentle parenting on the social and emotional development of early childhood, especially in the context of parenting culture in Indonesia. Through library observation methods and analysis of current literature, this research explores how the principles of gentle parenting, such as patience, empathy, and setting healthy boundaries, can increase children's self-confidence, independence, and self-regulation abilities. Findings show that children raised with this approach tend to have better relationships with their parents and show more positive behavior in social settings. In addition, this article also identifies the challenges parents face in implementing this method amidst societal expectations that often demand a more authoritarian parenting approach. In conclusion, gentle parenting has the potential to be an effective strategy in supporting holistic early childhood character development, but requires comprehensive understanding and consistent social environmental support.